2019
DOI: 10.1111/echo.14498
|View full text |Cite
|
Sign up to set email alerts
|

Biatrial and right ventricular deformation imaging: Implications of the recent EACVI consensus document in the clinics and beyond

Abstract: In this review, right ventricular (RV), right atrial (RA), and left atrial (LA) strain in some selected clinical situations has been discussed in light of the current literature. To exemplify the significance of the use of multichamber strain, we have provided some illustrations of common cardiac problems. The recently published European Association of Cardiovascular Imaging (EACVI) consensus document for standardization of RV, RA, and LA strain, using the currently available software, has fulfilled the aspira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Like the left atrium, RA deformation is a cyclic process, which can be sub-divided into three phases: the Reservoir phase, the Conduit phase and the Contraction phase. [40,50] Early impairment of left ventricular diastolic function will lead to significant reduction in right atrial and right ventricular strains. Vakilian et al [51] studied the non-invasive assessment of right ventricular hemodynamics in patients with heart failure (HFrEF) with reduced ejection fraction using right atrial strain.…”
Section: Assessment Of Right Atrial Functionmentioning
confidence: 99%
“…Like the left atrium, RA deformation is a cyclic process, which can be sub-divided into three phases: the Reservoir phase, the Conduit phase and the Contraction phase. [40,50] Early impairment of left ventricular diastolic function will lead to significant reduction in right atrial and right ventricular strains. Vakilian et al [51] studied the non-invasive assessment of right ventricular hemodynamics in patients with heart failure (HFrEF) with reduced ejection fraction using right atrial strain.…”
Section: Assessment Of Right Atrial Functionmentioning
confidence: 99%
“…As shown in Figure 1, bi‐atrial and right ventricular strain may provide useful diagnostic measures complementing the standard echo‐Doppler data. All the suggested cardiac comorbidities associated with CA, such as aortic stenosis, 1 atrial fibrillation, 2 and heart failure with preserved ejection fraction, have been shown to have diagnostic values using bi‐atrial and right ventricular strain 13 …”
Section: Measures Values Authors (References)mentioning
confidence: 99%
“…Not only that, in moderate to severe valvular pathologies, an abnormal diastolic stress test (elevated LAP, RVSP, E/Eʹ ratio, alone or in combination) may also offer convincing arguments in favor of early intervention. In subjects with moderate to severe aortic stenosis, an exercise‐induced elevated LAP or RVSP may be considered as “collateral damage,” prompting an early replacement of the diseased valve 10 Probably, the simplest of stress procedure could be a passive leg raise maneuver bedside, as has been illustrated in one of the contributions in this special issue by Henein and Lindqvist 11 …”
Section: Diastole At Rest or During Stress: There Is No Subclinical mentioning
confidence: 99%